Use of Lipat Algorithm on Android to Secure Data Communication in Social Media - Wintolo, Hero; Pujiastuti, Asih; Imam, Muhammad (SENATIK STT Adisutjipto, 2018)
Cryptography is one of science that learn about securing a message. Message security is done by randomizing the message (encryption) and returned to it’s original form (description). In this study, the designer of the system first and build an application to secure the message by using the Lipat Algorithm method that aims to secure messages consisting of letters, numbers, or symbols. Applications are designed and built running on Mobile Android. The Lipat Algorithm Method applies a fourfold system in the encryption process and the description of the message to be encrypted and in the description will advance 4 (four) characters forward or backward. Based on testing done the application managed to perform the encryption process and description correctly, ranging from short messages to messages as much as 2305 characters.